Perfil de metilação das ilhas CpG dos genes CDH1, TIMP3 E MGMT como fatores preditores para recidiva de neoplasia intraepitelial cervical em mulheres infectadas e não infectadas pelo vírus da imunodeficiência humana - Claudia Teixeira da Costa Lodi (2016)
Objective: To evaluate the profile of methylation in CpG islands of MGMT, TIMP3, CDH1 genes in human immunodeficience virus (HIV) infected and noninfected women with cervical intraepithelial neoplasia (CIN) recurrence or no recurrence. Method: Nested case-control study envolving 33 women with CIN recurrence (cases) and 114 without recurrence (controls), HIV infected (n=74) and noninfected (n=73), treated with loop electrosurgical excision procedure (LEEP), between January 1999 and May 2004.Recurrence diagnosis was established after biopsy. The methylation profile of the genes was assessed by methylation-specific quantitative PCR (MSQP) technique in formalin-fixed, paraffin-embedded cone specimens. Statistical analysis were performed to compare categorical variables, using X2 test with Yates correction and Fishers exact test. Multivariate analysis was carried out using a logistic regression. Results: CIN Recurrence was more frequent in HIV-infected women (OR 2,47; CI 95%: 0,87-7,05), and in those with compromised margins (OR 2,5; CI 95%: 0,87-7,27) and glandular involvement (OR 11,6; CI 95%: 2,93-45,89).There was no significant difference when compared methylation profiles of CDH1, TIMP3 and MGMT genes in relation to HIV infection, CIN grade and recurrence. At least one methylated gene, CDH1, TIMP3 and MGMT, was present in 85.1% HIV-infected women, in 91.6% women with CIN II/III and 87.9% women with CIN recurrence. Conclusions: Factors associated with recurrence were glandular involvement and compromised margins in cone biopsy and HIV infection. The profile of methylation in CpG islands of genes studied were not significant.